An Interpretative Phenomenological Analysis Of Experience Of Honorary Teachers Teaching Student With Disabilities In Inclusive Settings In Semarang. - Hardiyanti Rutmana; Achmad Mujab Masykur (Jurnal EMPATI, 2018)
The purpose of this study is to understand the experience of honorary teachers who teaching student with disabilities in inclusive settings. The study involved four female honors teachers 41-45 years old and had 8-12 years of teaching experience with disabilities students. This research using Interpretative Phenomenological Analysis (IPA) approach to understand the subject's experience through his personal life. In this study, semi-structured interviews were used as data collection methods. There are three main themes found: (1) early journey to become a teacher of  student with disabilities in inclusive settings (2) job description as teacher of student with disabilities in inclusive settings (3) appreciation about profession. The results of this study indicate that the four subjects are able to be grateful for the profession as a honorer teacher in inclusive settings with support from  interacting with children with disabilities  before their becoming a teachers,  supportive work environment, family support, comformity in work place and satisfaction in working help the four subjects to remain loyal to the their profession.